Potensi Kitosan Dalam Mengendalikan Infeksi Bakteri Streptococcus Agalactiae Pada Ikan Nila (Oreochromis Niloticus) - Ricko Reynalta; Putri Anugerah; Noorsheha Noorsheha; Uttari Dewi (KOLONI, 2024)
Streptococcus agalactiae are often the cause of Streptococcosis disease which attacks tilapia and results in mass death. Disease management needs to be done to control S. agalactiae infection using herbal ingredients and as an alternative to existing methods. The study consisted of two treatments (control and chitosan) of three repeats each. The treatment was tested in vivo by injection and challenged with S. agalactiae. Parameters observed include changes in morphology, fish behavior, and survival rates. The results of chitosan treatment on the parameters of changes in fish morphology and behavior showed milder infection than control, and a survival rate of 53.33%.